ANALISIS MITIGASI BENCANA ABRASI PADA WILAYAH PANTAI GALESONG KABUPATEN TAKALAR - Thania Aurel Sun Virgie Jumadil (Riset Sains dan Teknologi Kelautan, 2023)
Abstract Coastal areas are stressed by activities and phenomena occurring on land and at sea, including changes in coastal morphology such as abrasion and accretion. Recently, coastal erosion, also known as abrasion, has increased in many places. Coastal erosion itself can be caused by land subsidence, soil erosion, Mangrove Forest damage, damage caused by wave hydrodynamic forces, damage caused by abrasion, and damage caused by abrasion, residents lose residential, agricultural, and aquaculture land. Coastal abrasion is the retreat of the shoreline from its initial position. One of the problems that threatens the condition of the beach and shoreline is that it retreats, damaging ponds and rice fields on the seashore, and threatening structures directly adjacent to seawater.  As a result, most of the productive-aged residents have livelihoods as factory workers and construction laborers. As a result, they lost their livelihoods and also lost their income. The level of vulnerability of an area is influenced by a number of factors. These include the high density of population and vulnerable groups, the number of poor households and fishermen groups, the high density of settlements, and the lack of vegetation in coastal areas that are vulnerable to disaster threats. One way to mitigate abrasion disasters is to know the extent of damage caused by abrasion, know where abrasion occurs, and implement comprehensive and community-based coastal control.    Keywords : Abrasion, Disaster risk, Disaster impact, Abrasion prevention, Coastal area